The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fimmu.2016.00010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CD4 T Cell Memory in Generating Protective Immunity to Novel and Potentially Pandemic Strains of Influenza

Abstract: Recent events have made it clear that potentially pandemic strains of influenza regularly pose a threat to human populations. Therefore, it is essential that we develop better strategies to enhance vaccine design and evaluation to predict those that will be poor responders to vaccination and to identify those that are at particular risk of disease-associated complications following infection. Animal models have revealed the discrete functions that CD4 T cells play in developing immune response and to influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 67 publications
2
44
0
1
Order By: Relevance
“…It is becoming increasingly clear that viral protein specificity may be a key determinant in the effector program of influenza virus-specific T cells (25,(61)(62)(63). However, due to a lack of ferret-specific reagents, measuring antigen-specific CD4 and CD8 T cell responses has not been possible.…”
Section: Resultsmentioning
confidence: 99%
“…It is becoming increasingly clear that viral protein specificity may be a key determinant in the effector program of influenza virus-specific T cells (25,(61)(62)(63). However, due to a lack of ferret-specific reagents, measuring antigen-specific CD4 and CD8 T cell responses has not been possible.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion supports the model that the nature and complexity of the antigen taken up by antigen-specific B cells will determine the specificity of CD4 T cells that can provide help for expansion and production of high affinity antibodies. The abundance of these CD4 T cell specificities recruited into the response will likely provide the best correlate of protective antibody responses, with other viral antigen specificities either being neutral or negative (149). …”
Section: Provision Of Cd4 T Cell Help For B Cell Responses To Seasonamentioning
confidence: 99%
“…The abundance of these CD4 T cell specificities recruited into the response will likely provide the best correlate of protective antibody responses, with other viral antigen specificities either being neutral or negative. 149…”
Section: Analyses Of Human Responses To Avian Influenza Virus Vaccinesmentioning
confidence: 99%
“…Additional discussion focused on issues of CD4 T cell immunodominance and the nature of the Ag taken up by the HA-specific B cells after infection and vaccination. Also considered was that the contribution of CD4 T cells to the neutralizing Ab response may be either positive or negative, depending on the viral Ag specificity and the effector phenotype of the CD4 T cells (40). The discussion group suggested that the specific composition of administered influenza vaccines might have an important role in dictating long-term immunity.…”
Section: Influenza Vaccinesmentioning
confidence: 99%